THE HISTORY OF DEVELOPMENT OF POTTERY AND ITS PLACE IN APPLIED ART - Jumayeva Shahzoda; Qudratov Javlon Kholbazarvich (Journal of Higher Education and Academic Advancement, 2024)
This article contains a lot of scientific information about the history of the development of pottery and its role in practical art